Identifikasi Faktor-Faktor Wisata dalam Membangun Brand Image Kota Bandung - Usman, Maman; Pah, Jacob Ganef (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2018)
Bandung is a tourist town, trade and education. This is supported by the city of Bandung which lies relatively close to Jakarta as the capital of the Republic of Indonesia. Therefore, the city of Bandung is sensible to improve themselves or develop the city in order to be known by tourists both domestic and foreign. This research was conducted in the city of Bandung and the variables studied are factors that may increase the travel brand image of the city of Bandung. The purpose of this study was to determine the most dominant factor in travel to build Brand Image of Bandung. The sample in this study is the tourists who visit the city of Bandung. The sampling technique using the technique of accidental sampling and statistical analysis used was the Factor Analysis. The results showed that of the eleven major factor in building the brand image of the city of Bandung, namely recognition, affinity, reputation, domain, education, history, creative, culture, cultivation, entertainment and natural, factors protagonist of the most dominant decisive in building the brand image of the city bandung. Creative factor explaining Bandung city has many culinary and tourist attractions have a lot of shopping. This study suggested that the city of Bandung to the arrangement and structuring of regional culinary neighborhood shopping or put side by side with a culinary shopping tour, so that tourists no trouble finding the culinary or otherwise. The arrangement also aims to reduce congestion so that tourists feel safe and comfortable.